Zmiany przepisów w zakresie rachunkowości zabezpieczeń - Rosicka, Katarzyna (Changes in Hedge Accounting, 2005)
The article concerns hedge accounting as a method of presenting hedging in financial statement. It shows types of hedge accounting, major problems and conditions on which companies can use hedge accounting regulations. It also describes lately introduced changes and announce future changes in polish and European accounting law related with hedging.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 54-59